Effect of Different Organic Acids in Silage Preparation from Shrimp Shell Waste - S., Santhosh; T.K., Sini; P.T., Mathew (Fishery Technology, 2025)
The comparative effect of three commonly used organic acids in the production of silage from shrimp shell waste is hereby reported. Formic acid, lactic acid and citric acid were used at 5%, 6%, and 9% concentrations respectively. Samples were kept for 16 days and at an interval of three days, changes in pH, viscosity, protein content and mineral content were analyzed. Formic acid silage had the highest liquefaction and mineral content. Amino acid profile showed highest proportion of essential amino acids in formic acid silage. In silage prepared with lactic acid and citric acid, protein content and mineral content were very low. Chitin prepared from the shell residue of formic acid silage had good quality compared to others as supported by FTIR spectrum and mineral status.